2020
DOI: 10.1039/c9ja00268e
|View full text |Cite
|
Sign up to set email alerts
|

Cu-based alloys as a benchmark for T-PGAA quantitative analysis at spallation neutron sources

Abstract: In this paper, we present, for the first time, a quantitative analysis carried out using time-resolved prompt gamma activation analysis (T-PGAA), a technique currently under development at the ISIS pulsed Neutron and Muon Source in Oxfordshire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Resonances are observed by detecting the prompt-gamma radiation that is directly emitted after neutron capture as a function of the neutron energy. In recent years, attempts to measure both the neutron and gamma energies at the same time have been presented [65][66][67][68], in the so-called bi-parametric configuration, and one can foresee an ample range of applicability to Cultural-Heritage studies.…”
Section: (Nυ)-based Techniques (Radiative-capture Techniques)mentioning
confidence: 99%
“…Resonances are observed by detecting the prompt-gamma radiation that is directly emitted after neutron capture as a function of the neutron energy. In recent years, attempts to measure both the neutron and gamma energies at the same time have been presented [65][66][67][68], in the so-called bi-parametric configuration, and one can foresee an ample range of applicability to Cultural-Heritage studies.…”
Section: (Nυ)-based Techniques (Radiative-capture Techniques)mentioning
confidence: 99%
“…Arcidiacono et al reported the use of a neutron-based quantitative method entitled time-resolved prompt gamma activation analysis (T-PGAA) for the analysis of copper-based alloys. 29 This is a relatively new, technique developed by the authors and undertaken on an instrument designed and built in-house. A high purity germanium detector maintained at 77 K was used to acquire both the photon energy promptly emitted by the irradiated sample and the time at which the prompt gamma ray is detected.…”
Section: Metalsmentioning
confidence: 99%